A wearable computer for support of astronaut extravehicular activity - Carr,CE; Schwartz,SJ; Rosenberg,I (2002)
A wearable situational awareness terminal (WearSAT) that provides text, graphics, and video to an astronaut via a near-eye display, and acts as a client on a wireless network, has the potential to enhance the ability of astronauts to perform useful work and cope with uncertainty during extravehicular activity (EVA). An initial implementation is described, including the supporting network architecture, a hardware prototype, and the results of experimentation with a space suit to assess packaging options and evaluate a near-eye display for compatibility with EVA tasks. Operational scenarios are used to derive requirements for software development.